Financial Intensity or Project Duration: What Drives Patents and Spin-Offs in Public R&D Projects? - Evangelos Makryvelios; Theodore Papadogonas (Journal of Regional Economics and Development, 2026)
The aim of the research is to examine the aspects that govern the innovation outcomes of publicly funded Research and Development (R&D) projects at the project level, focusing on the intensity of funding, implementation period, and the resulting induced private investment. The empirical model relies on a sample of 1,435 projects in the Attica Region and approximates a log-linear econometric model with the OLS technique and heteroscedasticity-robust standard errors. The innovation performance is measured using the logarithm of the total number of patents and spin-offs generated by an individual project. The findings indicate that final project budget and induced private investment have a positive and statistically significant impact on innovation outcomes, with the largest impact being that of private leverage. Conversely, project implementation does not have an ordered contributor to patent and spin-off production.